Mesenchymal stromal cells primed with Paclitaxel attract and kill leukaemia cells, inhibit angiogenesis and improve survival of leukaemia‐bearing mice. (7th January 2013) - Pessina, Augusto; Coccè, Valentina; Pascucci, Luisa; Bonomi, Arianna; Cavicchini, Loredana; Sisto, Francesca; Ferrari, Maura; Ciusani, Emilio; Crovace, Antonio; Falchetti, Maria Laura; Zicari, Sonia; Caruso, Arnaldo; et al.
Summary Current leukaemia therapy focuses on increasing chemotherapy efficacy. Mesenchymal stromal cells (MSCs) have been proposed for carrying and delivery drugs to improve killing of cancer cells. We have shown that MSCs loaded with Paclitaxel (PTX) acquire a potent anti‐tumour activity. We investigated the effect of human MSCs (hMSCs) and mouse SR4987 loaded with PTX (hMSCsPTX and SR4987PTX) on MOLT‐4 and L1210, two leukaemia cell (LCs) lines of human and mouse origin, respectively. SR4987PTX and hMSCsPTX showed strong anti‐LC activity. hMSCsPTX, co‐injected with MOLT‐4 cells or intra‐tumour injected into established subcutaneous MOLT‐4 nodules, strongly inhibited growth and angiogenesis. In BDF1‐mice‐bearing L1210, the intraperitoneal administration of SR4987PTX doubled mouse survival time. In vitro, both hMSCs and hMSCsPTX released chemotactic factors, bound and formed rosettes with LCs. In ultrastructural analysis of rosettes, hMSCsPTX showed no morphological alterations while the attached LCs were apoptotic and necrotic. hMSCs and hMSCsPTX released molecules that reduced LC adhesion to microvascular endothelium (hMECs) and down‐modulated ICAM1 and VCAM1 on hMECs. Priming hMSCs with PTX is a simple procedure that does not require any genetic cell manipulation. Once the effectiveness of hMSCsPTX on established cancers in mice is proven, this procedure could be proposed for leukaemia therapy in humans.